High-throughput approaches for bioprospection to leverage natural product discovery and for single-cell persister phenotyping - Oberpaul, Markus; Justus Liebig University Giessen (My University, 2022)
Due to multifactorial causes, e.g. the spread of antimicrobial resistances, it is hypothesized that we may face a post-antibiotic era in the upcoming decades. Although pharmaceutical industry stopped or outsourced natural products research and development of antibiotics in the recent past, fresh inspirations have to be discovered steadily. One option to outpace this issue to aim on dismantling the ‘microbial dark matter’, which offer a vast and largely untapped chemical space that is ready to be investigated. To this end, the implementation of innovative high-throughput cultivation techniques is critical, which also facilitates the comprehensive exploration of diverse untapped bioresources and meet the needs of fastidious hitherto uncultured microorganisms. Thus, the imperative of an adaptive, and cost-effective high-throughput pipeline that is ready to uncover novel natural products from environmental microorganisms, was converted into an entire process ‘from bioresources to bioactive compounds’ within the framework of Fraunhofer IME-BR and Sanofi (later Evotec) Public-Private-Partnership (PPP). Social insects display an example for underexplored bioresources. Due to longtime evolutionary effects, a homeostasis of microbial symbionts was established, which supports defense mechanisms of nest inhabitants against invaders. It is known that lower subterranean termites lack of a great arsenal of antimicrobial peptides compared to numerous other insects. Thus, in the first chapter of this work, the focus was on the implementation of selective and adaptive cultivation techniques in order to make this untapped chemical space available. As a case study, the microbiota at different nest levels and in specimens of three subterranean termites (Coptotermes testaceus, C. gestroi and C. formosanus), which have been reared since decades before, were analyzed over a timeframe of 2 years. A stable core microbiome was determined, which was further confirmed by comparison to a nest suffering from a fungal infection. The analysis of the microbiome revealed a high abundance and diversity of Acidobacteria. They are interesting in terms of natural product research, however, few representatives are currently available. Therefore, a high-throughput microplate-based cultivation pipeline was applied to successfully integrate new Acidobacteria species in the Fraunhofer strain collection. This was brought to the next level by a prior cultivation step using droplet microfluidics in combination with fluorescence-associated cell sorting. Furthermore, the workload was rapidly minimized due to the identification of cultivated redundancy. This was facilitated by applying sophisticated metabolomic studies and UHPLC-HRMS/MS bioactivity-guided screening for chemical novelty, which sets new benchmarks for the utilization of microfluidics cultivation techniques combined with bioactivity-guided screenings. The pipeline facilitated the cultivation of a broad diversity of microbes from a common forest soil sample, including three new species in each genus Edaphobacter, Acidobacterium and Olivibacter, respectively. The integrated downstream metabolomics and screening pipeline led to the discovery of new bioactive derivatives of macrotetrolides, massetolides and cyclic lipopeptides in other species. Moreover, axenic cultures of Trichoderma sp. FHG000531 isolated from the nest of C. testaceus facing the fungal infection, and Olivibacter sp. FHG000416 isolated from the carton nest of C. gestroi were analyzed to characterize their chemical repertoire. This led to the identification of a novel pentapeptide (FE011) and five derivatives thereof, additionally three novel N-acyl-amino acids (NAAAs) two lipoamino acids (LAAs) and one lysophosphatidylethanolamine (LPE). Two of the LAAs showed a valuable bioactivity with a minimal inhibitory concentration (MIC) of 8-16 µg/mL and the LPE 16 µg/mL against the Gram-negative pathogenic bacterium Moraxella catarrhalis ATCC 25238. Relapsing nosocomial infections aggravate the spread of antimicrobial resistance. Thus, in the second chapter of this work, drug-induced persister formation of the model organism E. coli, which are facing phenotypic consequences, were analyzed in high-throughput fashion. To this end, a stationary-phase model to detail TisB-dependent persistence in E. coli was established (E. coli Δ1-41 Δist R), and a comprehensive single-cell persister phenotyping was achieved. This contributes to the understanding of drug-induced persister formation, which is urgent to develop approaches to overcome persister formation in e.g. wound infections. The high-throughput microfluidics-based cultivation pipeline and persister phenotyping supported by flow cytometry methods, which is presented in this work, will significantly contribute to natural product discovery. Thus, ultimately increasing the chances to combat the threat of the antimicrobial resistance crisis.
Hochdurchsatzmethoden zur Bioprospektion für die Naturstofforschung und zur Einzelzell-Persisterpänotypisierung
Keywords: Insects; Microbial Biotechnology; Trichoderma; Antibiotics; Anti-infectives; Termites; Natural Products Discovery; Acidobacteria; Microfluidics; Bacteriodetes; Toxin-antitoxin systems; Persistence; ddc:500; ddc:570